Archimedes and the Hydrostatic Balance - Lanza, Nasser Meneghetti; De Bortoli, Leomar (Scientia cum Industria, 2016)
The objective of this report is to discuss how Archimedes would have solved the problem of Hieron king's crown, addressing the solution mentioned by Galileo, proposing a discussion on the subject and seeking a resolution not only watertight . It is also proposed to show an educational alternative, which is a practical activity carried out with students of the Polytechnic School and regular, looking for a conceptual and historical linkage of science. Describes the critical line of Galileo, translated quotes of authors, lists a series of opposition elements to the story told in textbooks and present a proposal for qualitative analysis with concept maps, in search subsumers and evaluation of results after application of an activity using the hydrostatic balance. http://dx.doi.org/10.18226/23185279.v3iss3p77